2007
DOI: 10.1111/j.1399-0012.2007.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized lymphedema in a sirolimus‐treated renal transplant patient

Abstract: Generalized lymphedema is an extremely rare effect of sirolimus therapy in renal transplant recipients. We describe the development of this complication in a 56-yr-old woman, who was given an experimental protocol with cyclosporine, sirolimus, steroids, and basiliximab. Following the protocol, after one month, the patient was randomized to the "sirolimus only" group, while cyclosporine was completely suspended and the oral steroids were continued. Three months later, the patient was admitted for severe lymphed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
0
17
1
Order By: Relevance
“…Lymphedema, with or without ascites, pleural, and pericardial effusions have been reportedly improved by dosage lowering or discontinuing sirolimus in several renal transplant recipients. 2,5 Secondary lymphedema typically involves a single limb, while involvement that is more widespread may be seen in primary lymphedema. In our case, lymphedema began at the feet at the fifth month of everolimus therapy, and progressed to left upper limb and left breast within 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphedema, with or without ascites, pleural, and pericardial effusions have been reportedly improved by dosage lowering or discontinuing sirolimus in several renal transplant recipients. 2,5 Secondary lymphedema typically involves a single limb, while involvement that is more widespread may be seen in primary lymphedema. In our case, lymphedema began at the feet at the fifth month of everolimus therapy, and progressed to left upper limb and left breast within 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous formation of lymphedema has been seen with sirolimus-based immunosuppression in renal transplant recipients. [2][3][4][5] We report the first recipient who developed lymphedema 8 months after starting everolimus treatment.…”
Section: Introductionmentioning
confidence: 94%
“…It is also thought to be effective in the prevention and treatment of graft-versus-host disease. De Bartolomeis et al (4) have reported a case where the patient received sirolimus immunosuppressive therapy following renal transplantation and had bilateral lower extremity edema, acid, and dyspnea complaints at postoperative month 3. In this case, the result of the sequential parasynthesis for exploring the tumoral and infectious cause was negative, and after discontinuation of sirolimus therapy, lymphedema was reversed completely.…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus is a macrolide-group antibiotic that is isolated from Streptomyces hygroscopicus (4). Its use in preventing acute rejection after renal transplantations and in chronic allograft nephropathia is becoming increasingly common.…”
Section: Discussionmentioning
confidence: 99%
“…13 Interestingly, all these reported sirolimus-related cases (including ours) were diagnosed after at least 3 months use of sirolimus. [14][15][16][17] Therefore, early use of sirolimus in our case should not be neglected as a possible cause of delayed-onset chylous ascites.…”
Section: Discussionmentioning
confidence: 99%